2003
DOI: 10.1002/anie.200250690
|View full text |Cite
|
Sign up to set email alerts
|

Spirodiporphyrins—As Binuclear Metal Complexes

Abstract: Dedicated to Professor Ronald BreslowPorphyrin supermolecules constructed from multiple porphyrin moieties that are linked covalently [1] or coordinatively [2] by spacers have developed as an important line of research in porphyrin chemistry (with potential applications as electronic or optical functional units, sensors, and artificial photosynthetic devices). In contrast to these porphyrin supermolecules, the no less intriguing di-and oligoporphyrins devoid of spacers, that is, meso-meso-, b-b-or meso-b-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 35 publications
0
43
1
Order By: Relevance
“…Support for this mechanism comes from the behavior of bimetallic [36]octaphyrin(1.1.1.1.1.1.1.1), which splits into the two porphyrin macrocycles via the covalently linked spiro intermediates 13 (Scheme 3). [7,8] predominating at room temperature, and the equilibrium can be shifted photochemically to 11. [7] Osuka and co-workers discovered the ultimate transformation of the copper(II) complex of an octaphyrin into the corresponding spirocyclobutane intermediate 14, which was split into two porphyrin molecules 15 through a cycloreversion reaction (Scheme 4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Support for this mechanism comes from the behavior of bimetallic [36]octaphyrin(1.1.1.1.1.1.1.1), which splits into the two porphyrin macrocycles via the covalently linked spiro intermediates 13 (Scheme 3). [7,8] predominating at room temperature, and the equilibrium can be shifted photochemically to 11. [7] Osuka and co-workers discovered the ultimate transformation of the copper(II) complex of an octaphyrin into the corresponding spirocyclobutane intermediate 14, which was split into two porphyrin molecules 15 through a cycloreversion reaction (Scheme 4).…”
mentioning
confidence: 99%
“…[7,8] predominating at room temperature, and the equilibrium can be shifted photochemically to 11. [7] Osuka and co-workers discovered the ultimate transformation of the copper(II) complex of an octaphyrin into the corresponding spirocyclobutane intermediate 14, which was split into two porphyrin molecules 15 through a cycloreversion reaction (Scheme 4). [8,9] Although the formation of spiro compounds has so far only been experimentally observed for metal complexes, the close analogy between these reactions indicates the likelihood of their involvement in the reaction 8!9 as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we examined the metalation of 1 at the semiporphyrin-like pocket by treating 1 with a solution of Zn(OAc) 2 + : m/z 1767.0194) in its high-resolution electrospray ionization (HR-ESI) mass spectrum, and it exhibits a simple 1 H NMR spectrum that reveals its C 2 -symmetric structure in solution (Supporting Information).…”
mentioning
confidence: 99%
“…[4] Vogel et al revealed an interesting equilibrium of the dipalladium complex of octaphyrin(1.1.1.0.1.1.1.0) and its bis-spiro derivative, and isolated the dinickel complex of a spirodicorrole upon metalation of dioxooctaphyrin(1.1.1.0.1.1.1.0). [5] Both processes involved large skeletal rearrangements. We also reported that complexation of [36]octaphyrin(1.1.1.1.1.1.1.1) 1 with copper provided the dicopper(ii) complex 2, which underwent a quantitative thermal splitting reaction into two copper(ii) porphyrins, 3, through an unprecedented metathesis that involved the scission and formation of at least two carbon-carbon bonds.…”
mentioning
confidence: 99%